Abundance and Diversity of Ophiostomatoid Fungi Associated With the Great Spruce Bark Beetle (Dendroctonus micans) in the Northeastern Qinghai-Tibet Plateau - Wang, Zheng; Zhou, Qinzheng; Zheng, Guiheng; Fang, Jiaxing; Han, Fuzhong; Zhang, Xingyao; Lu, Quan (Frontiers in Microbiology, 2021)
The role of several virulent tree pathogens in host death has been overlooked because of the aggressiveness of their associated bark beetles. The great spruce bark beetle (Dendroctonus micans) is a widely distributed beetle that infests coniferous plants in Eurasia; however, its associated fungi have been poorly studied. Therefore, in this study, we elucidated the diversity of ophiostomatoid fungi associated with D. micans in the northeastern Qinghai-Tibet Plateau through field investigation, laboratory isolation, and culture analyses. A total of 220 strains of ophiostomatoid fungi were isolated from adults and tunnel galleries of D. micans infesting Picea crassifolia. We identified that the isolated strains belonged to eight ophiostomatoid species, including five new species (Ophiostoma huangnanense sp. nov., Ophiostoma maixiuense sp. nov., Ophiostoma sanum sp. nov., Leptographium sanjiangyuanense sp. nov., and Leptographium zekuense sp. nov.), one undefined species (Ophiostoma sp. 1), and two known species (Ophiostoma bicolor and Endoconidiophora laricicola), using phylogenetic analysis of multigene DNA sequences and morphological characteristics. This is the first time that E. laricicola, a pioneer invader and virulent pathogen, has been reported in China. We found that E. laricicola was the dominant species, accounting for 40.91% of the total number of ophiostomatoid communities. This study enriched the knowledge of the fungal associates of D. micans and elucidated that it carried the virulent pathogen E. laricicola at a surprisingly high frequency. Our findings show increased species association between D. micans and ophiostomatoid fungi and provide a basis for understanding the occurrence of forest diseases and pests.